Assessing the Authenticity and Validity of Tests in CLT-Based English Classrooms in West Java's Formal Education - Fella Rosy; Nida Husna; Ummi Kulstum; Muhammad Farkhan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study investigates the effectiveness of classroom tests in formal West Java, Indonesia, secondary learning centers that claim to offer Communicative Language Teaching (CLT). Because CLT places significance on fostering communicative competence that contains grammatical, sociolinguistic, discourse, and strategic dimensions, there are concerns that the testing protocols employed may not adequately reflect the communicative goals. The data were collected from four English as a Foreign Language (EFL) instructors through the use of a qualitative multiple case study design by way of document analysis and semi-structured web survey. It was found that, while respondents demonstrated satisfactory theoretical knowledge of communicative testing and the use of performance tasks such as interviews, role-plays, and spoken tasks incorporated into videos, full compliance with the tenets of CLT is restricted. Principal impediments to successful implementation are restricted professional development opportunities, large classes, restricted instructional hours, and institutional policies favoring grammar-based tests. It is the finding of this research that, despite professed adherence to CLT, test validity is inconsistent. It is its recommendation that teacher assessment literacy must be upgraded, wide-ranging training needs to be implemented, and institutional policies need to be redesigned to bring communicative test practices into closer correspondence to CLT ideals.